New species of mites in the genera Uropoda, Crinitodiscus and Uroobovella from Turkey (Acari: Mesostigmata: Uropodidae, Urodinychidae) - Bal, Durmuş A. (Zootaxa, 2006)
Three new mite species of the cohort Uropodina, Uropoda turcica sp. nov., Crinitodiscus ayyildizi sp. nov. and Uroobovella anatolica sp. nov., are described and illustrated on the basis of specimens collected from Turkey. Uropoda turcica sp. nov. and Crinitodiscus ayyildizi sp. nov. (Uropodidae) were collected from the Eastern Black Sea Region, and Uroobovella anatolica sp. nov. was collected from Eastern Anatolia. All new species presented here are endemic, and have not been collected from any other regions or habitats in Turkey. Adults and deutonymphs of Uropoda turcica sp. nov. and Crinitodiscus ayyildizi sp. nov., and adults of Uroobovella anatolica sp. nov. are described, and ecological information for the new species is given.